Pengaruh Kompetensi Amil dan Akuntabilitas terhadap Kepercayaan Muzakki pada LAZISMU Payakumbuh - Bayu Putra; Deviani Deviani (Universitas Negeri Padang, 2023)
The problem in this study is that the trust of muzakki in paying their zakat to LAZISMU Payakumbuh is still low. The purpose of this study was to determine the effect of amil competence and accountability on muzakki's trust in LAZISMU Payakumbuh. This type of research is quantitative. The population in this study were all muzakki at LAZISMU Payakumbuh. The population technique used is accidental sampling. Accidental sampling is a sampling technique based on chance. The data analysis technique used the t-test and F-test techniques. Based on the data analysis and discussion that has been described previously, it can be concluded that amil competence has no significant effect on muzakki's trust, this can be seen from the T-test of the Amil competence variable having a significance value of 0.625 > 0.05, thus the first hypothesis in this study was rejected. so that the competence of amil has no significant effect on the level of trust in muzakki and accountability has a significant effect on the trust of muzakk seen from the results of the T test the accountability variable has a significance value of 0.002 > 0.05, thus the second hypothesis in this study is accepted. so that accountability has a significant effect on the level of trust in muzakki.